1978
DOI: 10.1111/j.1365-2427.1978.tb01457.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biology of British Naididae (Oligochaeta) with emphasis on the lotic environment

Abstract: Naidlds live in a wide range of aquatic habitats but are particularly important numerically as part of the benthic fauna of rivers with stony substrates. In general they graze on bacteria and algae although some, particularly Oiaetogaster spp., are mainly predaceous, and C. Hmnaei vaghini is a parasite of molluscs, chiefly Gastropoda. Food selection seems to be based largely on particle size although the food quality of the particles within the appropriate size-range influences rates of growth and reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
12

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 56 publications
6
71
1
12
Order By: Relevance
“…Therefore, the stable food supply and temperatures could explain the absence of annual growth patterns in the WWTPs. This was also supported by asexual reproduction of the species in our research, which usually indicates favourable conditions like food availability, higher temperatures and low NaCl concentrations (Learner et al, 1978;Loden, 1981). In addition, top-down predation as observed in field situations by, for example, fishes (Wallace & Webster, 1996) is virtually absent from WWTPs, which is another explanation for the seemingly random population dynamics.…”
Section: Population Dynamicssupporting
confidence: 53%
“…Therefore, the stable food supply and temperatures could explain the absence of annual growth patterns in the WWTPs. This was also supported by asexual reproduction of the species in our research, which usually indicates favourable conditions like food availability, higher temperatures and low NaCl concentrations (Learner et al, 1978;Loden, 1981). In addition, top-down predation as observed in field situations by, for example, fishes (Wallace & Webster, 1996) is virtually absent from WWTPs, which is another explanation for the seemingly random population dynamics.…”
Section: Population Dynamicssupporting
confidence: 53%
“…Not surprisingly, Lumbriculidae and Tubificinae are known to prefer fine sediments (Dumnicka 1994;Verdonschot 2001) and were generally more abundant along the lake littorals where such substrates are more likely to occur, while Naidinae, which seemed to prefer coarse substrates (Learner et al 1978), were more frequently found in the lake outlets. Otherwise, the distribution of Enchytraeidae seemed to be determined by parameters other than substrate type and current velocity, because they could be numerically important in both littoral and outlet samples.…”
Section: Discussionmentioning
confidence: 99%
“…of these sub-families can be attributed to their lifestyles. Various species of Naidinae and Pristininae can disperse actively in the water column (Learner et al, 1978) and can thus more easily colonize different habitats, including decomposing organic material. In contrast, the Tubificinae live in direct contact with the substrate (Elissen et al, 2008) and are slow colonizers (Levin et al, 1996).…”
Section: Oligochaetesmentioning
confidence: 99%